Assessment of depression in elderly with systemic hypertension - Patrícia Costa dos Santos da Silva; Lidiane Aparecida Monteiro; Alessandra Domingues da Silva Graciano; Fábio de Souza Terra; Eugenia Velludo Veiga (Rev Rene)
We aimed to evaluate the presence of depression, the ability to perform activities of daily living, and the cognitive function of elderly with hypertension registered in a unit of the family health strategy. A descriptive-quantitative research conducted in Minas Gerais, Brazil, from December 2011 to January 2012, with 172 elderly patients, using a characterization instrument; the Yesavage Geriatric Depression Scale; the Katz Activities of Daily Living Scale; and the Mini-Mental State Examination. We found depressive symptoms in 30.2% of the sample, 93% of the elderly were classified as independent, 2.2% presented partial dependence, and 4.8%, total dependence. By associating the variables “ability to perform activities of daily living” and “depression”, we found a statistically significant difference. Thus, we concluded that elderly patients with hypertension present depressive symptoms in a percentage higher than that found in the general population and that most have the ability to perform activities of daily living.